Revitalization of Islamic Education Epistemology - Suripto (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2018)
Islamic education is faced with a very complex problem, on the one hand it must be able to transfer knowledge and on the other hand that is not less important is to transfer the value of Islamic teachings. Epistemological criticism of the concept of Islamic education actually lies in the conceptual-philosophical building of Islamic education that does not have a clear and functional concept in dealing with the development of science and technology. Islamic education experiences lethargy and does not have the power of vitality that is not capable of giving birth to the concept of science that is able to solve the problem of universal humanity because it is trapped in the confines of the dogma of theology and fiqh of medieval scholars.